USING A WHEEL PAIR WITH A COUNTER-FLANGE TO PREVENT DERAILMENT - Yuriy Iv. OSENIN; Larysa DEGTYAREVA; Galyna OSENINA; Oksana SERGIENKO (Transport Problems, 2017)
The authors propose an engineering solution for a wheel pair with a counter-flange that satisfies the existing standards of vertical and horizontal dynamics and the movement stability index. An improved profile of a rail wheel with a counter-flange is developed. It provides additional contact in the horizontal plane in the situation of transverse vibrations of the wheel pair against the rail track, adds to carriage stability and increases the wheel’s resistance to derailment when passing a curved part of the tracks or when rails deflect due to force interaction. The wheel pair profile is stabilized with an additional running track and counter-flange that prevents derailment when base flange of the wheel rolls onto the working surface of the rail or when there is a way spacer due to rail spring deformation. The proposed design of the wheel pair is covered by an Ukrainian utility model patent.